Perception of sources of private wealth: A qualitative study of perceptive schemes of Western and Eastern Bloc students - Joanna Pietrzak (International Journal of Management and Economics, 2021)
Over the recent years, money has become one of the most compelling topics in modern societies. Consequently, financial literacy turns out to be an indispensable ability in today's complex reality. Numerous studies reveal that the level of financial literacy is dependent on the socio-economic context in which the financial experience is formed. Against this background, this study aims to verify how the specific socio-economic context affects the perception of students with regard to the main sources of private wealth in the Western and Eastern Bloc countries. The research problem focuses on the following question: Do students' perceptions precisely reflect the economic reality in their countries? Data from 115 essays written by students from Poland, Austria, Russia, The Netherlands, Germany, Sweden, and Ukraine were analyzed using directed qualitative content analysis. A structured matrix of four predetermined sources of wealth - CEO compensation, financial trading, entrepreneurship, and inheritance - was developed and subsequently compared with students' observations. As a result, two conceptual models were developed presenting differences in the perceptive schemes of Western and Eastern Bloc students. Then the perceptions were compared with empirical data from the Forbes list of billionaires. This paper provides an example of how essays written by students can become a source of empirical research. Its added value lies in showing the usefulness of directed qualitative content analysis in socio-economic studies.
Keywords: Z1; F6; I3; J7; 650; wealth; income; financial literacy; socio-economic differences; directed qualitative content analysis